Cervical cancer in a patient from low socioeconomic group: a case study of tertiary prevention - I., Suriani; S. M., Saliluddin; M. M. D., Zulhusni; A. R., Nur Amirah (Community Health Society Malaysia, 2016)
Introduction: Cervical cancer is ranked fourth globally and second in Malaysia as the most common cancer in women. Despite having good prognosis if detected early, most cervical cancer cases in Malaysia unfortunately come in late for treatment. Case report: This is a case study of a 39 year old Malay lady who was diagnosed with cervical cancer stage IVB with metastasis to lungs, ovary, rectum and urinary bladder. Due to her financial predicament she had initially refused treatment, thus had delayed surgical intervention (bilateral salpingo-oophorectomy and omentectomy). She also had a history of defaulting on her scheduled chemotherapy treatment which could be atrributed to financial problems and cultural beliefs. However, currently she is back on chemotherapy and follow-up at the hospital, plus she is on continuous urine catheterisation while her Activities of Daily Living (ADL) is much compromised. Although chemotherapy for this patient is meant to relieve her symptoms, many aspects of her palliative care could be improved with increased knowledge and support from the relevant authorities and organizations. Conclusion: This report looks at the progress of a patient with cervical cancer stage IVB from a very low socioeconomic group who came very late for diagnosis and treatment, while having a history of defaulting treatment.